1 fm/?Hz noise level low temperature Fabry-Perot atomic force/magnetic force microscope operating in 4-300 K temperature range - Karc, Ozgur; Celik, Umit; Oral, Ahmet (Aip Publishing, 2020)
In this publication, we describe the design of a new fiber Fabry-Perot interferometer and employ this to a low temperature atomic force/magnetic force microscope (LT-AFM/MFM) operating in the 4-300 K temperature range. A multilayer dielectric mirror coated optical fiber is used to achieve unprecedented 1 fmnoise level, while the shot noise limit is 0.51 fm. The cavity length is adjustable, and the fiber can be brought within a very close proximity of the cantilever using a dedicated 2 mm stroke piezonanopositioner integrated on the piezotube scanner. The same nanopositioner also is used to park the fiber at a safe parking location during cantilever exchange. We demonstrate the performance of the LT-AFM/MFM by imaging the ITO thin film at 300 K, atomic steps on HOPG at 300 K, magnetic bits on the hard disk at 15 K, and the Abrikosov vortex lattice in the BSCCO(2122) single crystal at 4 K. Published under license by AIP Publishing.
Keywords: Interferometer; Cantilevers